THU0205 THE HEMATOPOIETIC STEM CELLS (HSCS) IN SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) REPROGRAM THEIR TRANSCRIPTOME: IMPLICATIONS FOR THE PATHOGENESIS OF THE DISEASE. (June 2019) - Banos, Aggelos; Grigoriou, Maria; Filia, Anastasia; Pavlidis, Pavlos; Giannouli, Lina; Karali, Vassiliki; Nikolopoulos, Dionisis; Pieta, Antigoni; Mitroulis, Ioannis; Verginis, Panayotis; Boumpas, Dimitrios
Abstract : Background: In SLE, all terminally differentiated blood cells demonstrate an aberrant phenotype. HSCs the most primitive cell type of the hematopoietic lineage when exposed within the bone marrow (BM) to adjuvants and inflammatory mediators change their transcriptional landscape and this may persist in the HSCs circulating in the peripheral blood or those infiltrating peripheral tissues. Within peripheral tissues these reprogramed HSCs differentiate into myeloid cells mounting enhanced protective or aberrant immune responses 1 . Objectives: To dissect whether aberrant phenotypes of blood cells in SLE could be traced back to HSCs and explore how the inflammatory environment of SLE shapes the HSC differentiation process. Methods: We analyzed the transcriptional alterations (genetic or epigenetic) of CD34 + cells in the BM of SLE patients, compared it to healthy individuals and the NZB/W lupus mice at the onset of disease (6 months). CD34 + cells were isolated from BM aspirates and peripheral blood of SLE patients (n=8) and healthy subjects (n=2) with magnetic separation (Stem Cell Technologies). mRNA was extracted and libraries were prepared. Sequencing was performed in NextSeq Illumina Platform. Alignment in human genome v.38 was done by Star package and differential expression analysis was performed by edgeR algorithm. Genes with FC≥1.5/≤-1.5, FDR≤0.05 were considered statistically significantly up-/down-regulated, respectively. Heatmaps were constructed in R, GO/Pathway Analysis and enrichment analysis were performed in ClueGo, RNEA, GeneMania and GSEA, respectively. Results: Overlaying the transcriptome of BM-derived CD34 + of SLE patients and healthy subjects, we identified in total 598 differentially expressed genes(DEGs) (82 up-/514 down-regulated in SLE). DEGs participate in hematopoietic cell lineage fate, regulation of stem cell differentiation, cell adhesion and cell cycle regulation. We also found evidence for cell cycle checkpoints signature which drives HSCs to experience replication stress and activate ATR pathway. Comparison of CD34 + profile between severe-moderate SLE reveals a prominent neutrophilic signature in severe disease. Comparative transcriptomic analysis of human vs murine SLE revealed a panel of common genes again related to cell proliferation, differentiation and platelet activation. Conclusion: HSCs in SLE patients and murine lupus reprogram their transcriptome in response to the inflammatory milieu within the BM, thus exiting from dormancy, differentiating to myeloid cells and mounting a DNA damage response to the replication stress. This activated phenotype renders HSCs both susceptible to cell exhaustion while at the same time priming them and their progenies towards enhanced immune responses. References: [1] Mitroulis, Ioannis, et al. "Modulation of myelopoiesis progenitors is an integral component of trained immunity." Cell 172.1 (2018): 147-161. [2] Kaufmann, Eva, et al. "BCG educates hematopoietic stem cells to generate protective innate immunity against tuberculosis." Cell 172.1 (2018): 176-190. Acknowledgement: This work was supported by FOREUM, IKY and ERC-Advanced Grant. Disclosure of Interests: None declared